Keterampilan Mengajar dan Komunikasi Interpersonal Guru Sebagai Determinan Terhadap Hasil Belajar Siswa dan Motivasi Belajar Siswa - Dwi Indah Artaverlina; Siti Sri Wulandari (Edunusa: Journal of Economics and Business Education, 2021)
This research is focused on four variables, namely teacher teaching skills, teacher interpersonal communication, student learning motivation, and student learning outcomes at SMK Krian 2 Sidoarjo, East Java, to be precise in the OTKP (automation and office management) department of OTK Public Relations and Protocol subjects. This study processed primary data obtained from questionnaires that were distributed to 67 students as a sample. The analysis tool used is Partial Least Square. The results showed that teachers' teaching skills on student learning outcomes had a positive and also insignificant effects, of teacher interpersonal communication had no effect on student learning outcomes, student learning motivation had a positive and insignificant effect on student learning outcomes, teaching skills had a positive and significant effect on student learning motivation, teacher interpersonal communication has a positive and significant effect on student learning motivation, teaching skills have a positive and significant effect on teacher interpersonal communication, student learning motivation has a positive and insignificant effect on teaching skills and student learning outcomes, student learning motivation had the positive and insignificant effect of mediating communication about teacher interpersonal with student learning outcomes, teacher interpersonal communication has a positive and insignificant effect on mediating teaching skills with student learning outcomes